Settlement Control of Soft Ground using Cement-Ricehusk Stabilization - Chan, C-M.; Mokhtar, M. (Civil Engineering Dimension, 2012)
Cement is widely used for improvement of soft soils, but financial and environmental concerns are causing genuine concerns to all parties, leading to the quest for alternative and effective stabilizers. Ricehusk is an agricultural waste in Malaysia, commonly disposed of by open burning or dumping in landfills. Considering that the ashes derived from ricehusk are pozzolanic in nature, there is a possibility that a cement-ricehusk mixture could effectively improve soft soils with reduced cement dosage. This study examines the mixture’s effectiveness by monitoring the settlement reduction in a clay soil. Standard oedometer tests were carried out on a soft marine clay sample admixed with cement-ricehusk. Test specimens contained 0-10% cement and 0-5% of ricehusk respectively, and were left to cure for either seven or 28 days. The stabilized specimens were observed to undergo significant reduction in compressibility, verifying the potential of cement-ricehusk as an alternative soft soil stabilizer.